The Clinical Generational Interview. An instrument for family assessment - Tamanza, Giancarlo; Gennari, Marialuisa (Frontiers in Psychology, 2024)
Interviews are the privileged tool for carrying out qualitative research and clinical assessments on family relationships. Nevertheless, there are limited examples of interviews in clinical and psychosocial literature that are explicitly aimed at the evaluation of relational-family constructs. This paper presents the essential characteristics of the Clinical Generational Interview (CGI): an original tool for investigating and evaluating family relationships, that aims to combine the complexity of the subject being studied with the systematic and rigorous approach. It was created according to the following criteria: a flexible qualitative approach, the production and relational reading of information, intersubjective measurability and control of the inferential/interpretative process, and clinical use.Although it is organized in a structured and well-defined form and provides a precise system for encoding information, it is not a test, nor an algorithm that can be used in a mechanically diagnostic sense; it is a very versatile psychological tool that can be used in two different areas: the first is related to clinical research on family and couple relationships, the second to relational assessments.The contribution illustrates the path of construction and elaboration of the instrument, considering first of all its theoretical foundations and the constructs derived from them and around which the set of items is organized. The criteria for coding and analyzing the information thus produced and the different possible areas of application are then described. Finally, the theoretical and methodological characteristics of the instrument are also considered in relation to the main interviews in the literature in order to highlight differential particularities.